Pengembangan Karir Mahasiswa Berbasis Kurikulum Merdeka: Analisis Praktik Kerja Lapangan Di Fakultas Ekonomi Dan Bisnis Islam - Dhinda Vadya Izmi (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to identify and find new ways to develop students' careers based on the independent curriculum through the analysis of field work practices. To achieve this goal, the researcher used a qualitative research method with a descriptive approach. Data was collected through a questionnaire questionnaire given to students who play an important role in field work practices at the Faculty of Febi IAIN Lhokseumawe. There were 4 students who became sources of information in this study and 1 lecturer. The results of this study include several things, among others: 1) Career development planning in higher education, 2) Types of career development programmes implemented, 3) Implementation and evaluation of field work practices, and 4) The effectiveness of independent curriculum-based career development implemented. Field work practices, workshops, and seminars carried out turned out to be able to improve student competence in career development.